CREATING AN ENGLISH-SPEAKING DIGITAL LEARNING ENVIRONMENT FOR PRESCHOOLERS: LINGUODIDACTIC ASPECT - Oksana Khomyshak (Інформаційні технології і засоби навчання)
Recent changes in the Ukrainian language policy have drawn public attention to the issue of shaping an English-speaking digital learning environment for preschool children and have urged researchers to examine the matter from the standpoint of linguodidactics. The pedagogical benefits of mastering English as a second language by preschoolers alongside their mother tongue and their native culture have been studied. A thorough analysis of language acquisition theories has been made in the article. In the context of sociocultural theory, the core role of parents (caregivers) as the child’s initial teachers (pedagogues) and creators of English digital learning environment is outlined. The author has provided guidelines on learning English as a second language based on the supportive use of digital learning tools in English at an early age. The article provides a definition of the term English-speaking digital learning environment. The current research showcases the use of digital learning tools for interpersonal and intercultural communication between adults and a child. The didactic value of English vlogs and cartoons as the most interesting and engaging audiovisual support for children’s English language communicative competence formation is determined. The author provides case examples of how game techniques of miming, dressing up, dramatising, acting out and role-playing cartoons and vlogs scenarios may be employed. A number of online educational platforms and applications designed for learning English have been analysed according to target audience, objectives, content, linguistic, and didactic accuracy. The author has designed a framework of English-speaking digital learning environment formation on three levels: family, educational institutions, and state. The effectiveness of the suggested guidelines on how to create a favourable English digital learning environment for preschool children has been corroborated on the basis of questionnaires and interviews with parents in the kindergarten.